Predation attempt by a White-throated Monitor Varanus albigularis albigularis (Daudin, 1802) on a free-tailed bat (Chiroptera: Molossidae) in South Africa, with a review of chiropterans in the diets of varanids (Squamata: Varanidae) - (:unkn) unknown (My University, 2023)
Predation attempt by a White-throated Monitor on a free-tailed bat in South Africa, with a review of chiropterans in the diets of varanids.
Keywords: African Research